Virginia history in documents collection - Gaines, William H. (William Harris), 1918-
Facsimiles of documents in Virginia colonial history concerning subjects such as individual rights, national unity, and self-government. Documents include an ordinance and constitution for a council and assembly in Virginia, July 24, 1621; Nathaniel Bacon's Declaration of the People, against Sir William Berkeley, July 30, 1676; Patrick Henry's resolutions against the Stamp Act, May 30, 1765; proceedings of a meeting of representatives in Williamsburg, May 30, 1774; resolutions of the Virginia Convention for independence, May 15, 1776; the Virginia Declaration of Rights, June 12, 1776; A Constitution, or form of government, June 29, 1776; A Bill for Establishing Religious Freedom, proposed June 12, 1779, passed, January 16, 1786; resolutions for the cession of lands to the United States, January 2, 1781; and form of ratification of the United States Constitution, June 25, 1788.
Includes a copy of William H. Gaines's book titled Virginia History in Documents, 1621-1788, published in 1974, which includes typewritten transcripts of the documents.
In part, facsimiles of originals in various repositories.
Various repositories.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Bacon, Nathaniel, -- 1648-1676.; Berkeley, William, -- Sir, -- 1605-1677.; Henry, Patrick, -- 1736-1799.; Great Britain; United States; Virginia; Virginia; Virginia; Virginia. -- Convention -- (1776 May 6-July 5); Virginia. -- Council; Virginia. -- General Assembly; Freedom of religion -- Virginia; Human rights; Nationalism -- United States; Representative government and representation; Northwest, Old -- History -- 1775-1865.; United States -- Politics and government -- 18th century; Virginia -- History -- Colonial period, ca. 1600-1775.; Virginia -- History -- Revolution, 1775-1783.; Virginia -- Politics and government -- Colonial period, ca. 1600-1775.; Virginia -- Politics and government -- Revolution, 1775-1783.